Comparative Analysis of Active and Passive Portfolios with the Single Index Model and Capital Asset Pricing Model in Indonesia: Policy Directions in the Capital Market - Sudarmadji, Harrys; Sudaryo, Yoyo; Sofiati, Nunung Ayu; Ismail, Gurawan Dayona; Sumawidjaja, Riyandi Nur (Journal of Public Representative and Society Provision, 2025)
This research conducts a comparative analysis between active and passive investment portfolios using two fundamental models in finance: the Single Index Model (SIM) and the Capital Asset Pricing Model (CAPM). The study focuses on stocks traded on the Indonesia Stock Exchange (IDX) that were not consistently included in the prestigious LQ45 Index during the period from January 2015 to June 2025. Using a rigorous quantitative method, the research compares portfolio performance, return, and risk under different strategies. The results conclusively indicate that portfolios designed with the Single Index Model consistently outperform those based on CAPM, and that active strategies deliver superior performance compared to passive ones. Beyond financial performance, the findings also carry significant policy implications. The consistent superiority of SIM suggests that regulators and market authorities should integrate simplified yet effective portfolio models into investor education initiatives. Similarly, the outperformance of active strategies highlights the importance of strengthening corporate disclosure standards and ensuring fair access to timely information, so that both institutional and retail investors can benefit equitably. By linking quantitative evidence with governance concerns, this study provides valuable insights for investors while offering policy directions to enhance transparency, inclusivity, and investor protection in Indonesia’s capital market.